Pocket park model for enhancement of social-learning experience in public universities in Malaysia - Salih, Sarah Abdulkareem Salih (2021)
Recently, outdoor learning spaces have become a necessary tool to improve the academic experience by enhancing students' social and learning activities. Globally, most of the universities are utilising outdoor learning spaces for social interaction, formal and informal learning. Investigating the visions of the Malaysian universities shows that the universities focus mainly on formal indoor learning and lack absorption of informal and formal outdoor education that meets academic outcomes. There is hence a need to enhance the social and learning activities of different students on-campus ground in order to improve the social-learning experience in Malaysian public universities. This study aims to develop a pocket park model for enhancing outdoor social and learning activities in order to enhance the social-learning experience in Malaysian public universities, and this is in line with the eleventh Malaysian plan 2016-2020. The study employs, first, a systematic review and content analysis to collect the primary data for designing the questionnaire survey. The main method involves a verbal and visual quantitative survey conducted in three public universities, including Universiti Malaya (UM), Universiti Putra Malaysia (UPM), and Universiti Kebangsaan Malaysia (UKM), to assess students' attitudes toward the pocket park model that proposed to enhance students' on-campus activities. The quantitative data were collected from 401 respondents using a simplified formula of Yamane (1967). Finally, a focus group discussion with nine experts in the fields of architecture, planning, landscape, and academics conducts to validate the collected data of the survey. The results reveal that successful pocket parks on-campus ground is significant for improving the on-campus activities and academic social-learning experience by implementing the highest characteristics and attributes of these pockets. Factors of the pocket park affecting students' overall social and learning activities on-campus ground included elements and activities, shade, sociability, proximity, facilities, participation, environmental factors, and noise level. The preferred attributes of the pocket parks to enhance overall social learning included mixed ground-covers, variety in softscape and hardscape, a solid shading device, and various activities. Yet, the characteristics and attributes of pocket parks vary according to different types of social and learning activities and users' demographics. The results also indicate that the curriculum and responsible authorities should enhance the implementation of on-campus activities to encourage the students to use the nearby pocket parks. The findings contribute to the development of a pocket park model in Malaysian public universities for integrating nearby open spaces in social and learning activities to improve the academic social-learning experience. Hence, the findings of this study are essential for academic administration, policymakers, landscape, and urban planners, as well as researchers in this field, in creating livable, educational, and socially responsive campuses.